Optimization, Characterization, and Anticancer Potential of Silver Nanoparticles Biosynthesized Using Olea europaea - Felimban, Afnan I.; Alharbi, Njud S.; Alsubhi, Nehad S. (International Journal of Biomaterials, 2022)
Green synthesis has attracted significant attention as an eco-friendly, low-cost, energy-efficient, and non-toxic method for preparing silver nanoparticles (AgNPs) for cancer therapy. This study optimized the green synthesis of AgNPs using Olea europaea extracts and evaluated their anticancer potential. The biosynthesized AgNPs were characterized using various methods, showing stable AgNPs with a desirable morphology and high yield, improving the properties of AgNPs for various medicinal applications. The biosynthesized AgNPs were predominantly spherical, with small sizes ranging from 13 to 21 nm and highly stable at −23 and −24 mV. The findings of this study suggest that green-synthesized AgNPs using Olea europaea and sunlight possess significant anticancer activity against cancer cells in vitro. Further investigation of green synthesis would help to form high-quality AgNPs that have promising potential in treating disease and fighting undesirable pathogens.